MyMosqueNet2Cloud collaborative system: a network of mosques towards eradicating poverty in Malaysia - Hamid, Habiba; Khairuddin, Nur Dini; Al-amodi, Yousra; Ahmad Dahlan, Abdul Rahman; Ahmad H.Osman, Rahmah (American Academy and Scholarly Research Center, 2013)
This paper proposes a conceptual collaborative system based on the deployment of the (a) Quadruple Helix Model (QHM), where a country's economic structure lies on four actors namely: academia, industry, government, and citizen, and the economic growth are generated by the clustering and concentration of talented and productive actors; (b) “Whole of-Government” (WoG) implementation that demands for a collaborative and co-operative arrangement of open consultation, open data, shared knowledge and expertise, consolidation of shared services and enhanced horizontal application across government agencies; and (c) citizen-centric Network-of-Mosques (NoM) – and focusing on achieving a higher quality of life and sustainable prosperity for all poor families in Malaysia. The proposed system, called MyMosqueNet2Cloud Collaborative System, will be accomplished through leveraging the advances in cloud computing and mobile applications. The System will expand the use of the eKasih database, managed by the Department of Social Welfare (DSW), and it can be used and updated by all other relevant government agencies. This proposed collaborative inter-organizational system is to enable a consolidated approach for government agencies, NGOs,the private sector and individuals in building up a single and trusted national database based on the poor families in Malaysia. This database, proposed to be co-owned and managed by government agencies such as DSW and Department of Islamic Development Malaysia (JAKIM) through NoM, can be used and updated by all other authorized organizations and individuals in making a consolidated contribution in nurturing and developing the poor families. Thus, this System shall eliminate unnecessary silos in efforts as well as duplication in data. The expected outcome of the System will be an enhanced quality of life for the poor families through the execution of government-led programs such as eKasih and 1Azam, with close collaboration with other QHM actors.